2018
DOI: 10.1080/21580103.2017.1420701
|View full text |Cite
|
Sign up to set email alerts
|

The influence of indirect nature experience on human system

Abstract: A growing number of studies have shown that contact with nature contributes enhancing positive psycho-physiological effects. This study experimentally compared the effects of direct and indirect contact with nature on psychological and physiological affect, respectively. Thirty university students participated in this experiment. The results of this study indicated that indirect nature experience also provided positive psychological and physiological effects, except for parasympathetic nerve activity. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The No.1 to No.6 groups were assigned to watch the No.1 to No.6 videos, respectively. Considering substantial previous research had proved the beneficial effects of direct and indirect contact with forests on the human body [24][25][26]31,32], no control group was set up in this study. Each participant was given a schedule for the experiment and was asked to be in the experimental room on time.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The No.1 to No.6 groups were assigned to watch the No.1 to No.6 videos, respectively. Considering substantial previous research had proved the beneficial effects of direct and indirect contact with forests on the human body [24][25][26]31,32], no control group was set up in this study. Each participant was given a schedule for the experiment and was asked to be in the experimental room on time.…”
Section: Participantsmentioning
confidence: 99%
“…With the rapid development of image projection technology, many studies have confirmed that the beneficial effects of forests on humans are still present when using displayed images [30]. Some studies have also compared the benefits of direct and indirect nature stimuli on humans and found no significant difference between them [31]. As an emerging method of image research, videos can show landscapes more realistically and comprehensively in a three-dimensional space.…”
Section: Introductionmentioning
confidence: 99%
“…De Kort et al [32] conclude that immersion enhances the restorative potential of a mediated natural environment but an interaction between screen size and restorative phase exist. An interesting investigation based on VR is the effectiveness of virtual nature in respect to real visit [33]. The authors affirmed that indirect nature experience also provided positive psychological and physiological effects, except for parasympathetic nerve activity.…”
mentioning
confidence: 95%
“…Comparative studies on the changes of individuals' emotional, cognitive, and physiological status when they walk in natural green spaces and urban built environments reveal the promoting role of natural experience on mental health [36] [37] . The control study at the virtual lab shows that watching images of natural landscapes (indirect nature experience) helps relieve mental pressure as well [38] .…”
Section: 研究地点mentioning
confidence: 99%